Investigating the Links Between Performers’ Self-Compassion, Mental Toughness and Their Social Environment: A Semi-Systematic Review - Kosirnik, Celine; Antonini Philippe, Roberta; Pomini, Valentino (Frontiers in Psychology, 2022)
Being mentally tough while evaluating oneself in a compassionate way is still a difficult path for performers. Self-compassion, characterized by the ability to be kind to oneself, to see one’s experiences as part of the larger human experience and have a balanced awareness to one’s emotions and thoughts, was recently studied as a stepping stone to performance optimization and personal development. Despite a mistrust of this concept in the sports world, various studies show its benefits within athletes. A major question remains the environment that fosters or hinders the development of self-compassion: when role models extend compassionate attitudes, does it allow performers to respond in more self-compassionate ways? The relationship between self-compassion, mental toughness, and social environment is still unclear and is an important direction for future research within performers. This semi-systematic literature review aims at proposing an overview of the state of the art regarding self-compassion, mental toughness, and the influence of performer’s, and social environments. Sixteen studies were retrieved. We conclude that the number of multi-day intervention programs and longitudinal studies should be increased. The studies should also consider assessing the specific aspects of performance culture and settings. In addition, overall performance-specific measures could be developed to assess general levels of self-compassion. The development of a theoretical framework explaining how self-compassion affects a performer, the role of their entourage and its link to other psychological resources, such as mental toughness, could help to better understand this concept.